ONLINE TEACHING: SOME BURNING OBSERVATIONS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Time is changing very fast. Globalization and privatization have shifted the entire focus of education on quality. Quality of education is spreading Quality of education plays pivotal role in the process of development of nations. Quality concerns in education are national priorities for all nations. For this very purpose, digitalization came into existence to solve the problem of scarcity of good teacher and arability of good material. Now, a student sitting in a village can learn from a teacher sitting in big cities or abroad. But as we know that every coin has two sides. So, online learning can help the students a lot, but due to lack of practical teaching- learning experience, most of the students cannot maintain their focus on the teaching while learning online. The present endeavor aims at finding out the realities of merits and demerits of online teaching-learning along with how tow to make online teaching boon to children sitting in village, especially girl students.